2021
DOI: 10.1016/j.pmedr.2021.101363
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation or initiation: The paradox of vaping

Abstract: Highlights The number of people vaping, especially adolescents, has surged in recent years. Studies of vaping as a smoking cessation tool have been largely inconclusive. Studies have produced compelling evidence linking vaping to smoking initiation . Early vaping studies have revealed numerous detrimental effects on the body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In fact, substantial evidence from several studies has shown that smoking e-cigarettes is linked to subsequent conventional cigarette initiation. A study has shown that the likelihood to be a conventional cigarette user is five times more among current e-cigarette smokers [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, substantial evidence from several studies has shown that smoking e-cigarettes is linked to subsequent conventional cigarette initiation. A study has shown that the likelihood to be a conventional cigarette user is five times more among current e-cigarette smokers [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…More evidence suggests that e-cigarette use is linked to smoking addiction, especially in adolescents. 54 Supporters of e-cigarettes believe that their devices replace high-risk behaviour, such as smoking traditional cigarettes, with a far less harmful one. In contrast, the opponents of e-cigarettes focus on the risks to adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…There is mixed evidence on the effectiveness of e-cigarette use for smoking cessation. Studies that show some effectiveness of e-cigarettes as a smoking cessation tool tend to examine smokers with high nicotine dependence ( Al-Hamdani & Manly, 2021 ). The potential benefits of e-cigarette use for quitting smoking have to be balanced with the potential for smoking initiation.…”
Section: Introductionmentioning
confidence: 99%
“…The odds of smoking initiation are 3.25 times higher for e-cigarette users vs non-e-cigarette users, and odds of relapse are 2.87 times higher among former smokers who are e-cigarette users vs non-e-cigarette users ( Baenziger et al, 2021 ). Further, the risks associated with e-cigarette use and smoking initiation among youth cannot be overlooked ( Al-Hamdani & Manly, 2021 ). The fact that less than one-third of ex-smokers or current smokers who used e-cigarettes did so for smoking cessation and that more than half of adolescent e-cigarette users have no history of smoking cigarettes suggests a net disadvantage of e-cigarette use ( Fulton et al, 2018 , Health Canada, 2015 ).…”
Section: Introductionmentioning
confidence: 99%